Achievements in pyrolysis process in E-waste management sector. (15th October 2021) - Joo, Junghee; Kwon, Eilhann E.; Lee, Jechan
Abstract: Many aspects of modern life of our civilization are associated with using electrical and electronic devices (EEE). Ever-increasing demand for high-performance EEE and accelerated technological development make the replacement of EEE become frequent. This leads to the generation of a tremendous amount of electronic waste (E-waste). Challenges of the management of E-waste have recently arisen out of a dearth of proper technologies to treat E-waste. Pyrolysis process can thermochemically treat waste materials that have a complicated nature and inhomogeneity. This article gives a systematic review as an effort to tackle the challenges in the context of achievements in pyrolysis process in E-waste management sector. Pyrolysis mechanism and types of pyrolysis processes and pyrolysis reactors are first discussed. Various pyrolysis technologies applied to the E-waste treatment are then summarized and compared to each other. Points to be considered for further research and pending challenges of E-waste pyrolysis are also discussed. The pyrolysis treatment of E-waste is not yet fully industrialized mostly because of high costs. However, there should be much room for further developing the E-waste pyrolysis; hence, its industrialization and commercialization is just a matter of time. Graphical abstract: Image 1 Highlights: Ways to treat E-waste via various pyrolysis processes are discussed. Types of pyrolysis processes and reactors used for E-waste treatment are discussed. Challenges and prospects for the E-waste treatment via pyrolysis are highlighted.